2021
DOI: 10.15282/ijim.11.1.2021.6131
|View full text |Cite
|
Sign up to set email alerts
|

Cost Estimation Performance in the Construction Projects: A Systematic Review and Future Directions

Abstract: Cost estimation in construction project is very critical for avoiding cost overrun in the project. This paper aims to provide a basis for improving cost estimation performance in construction through a systematic review of previous studies for last 31 years. The papers have identified a total of 238 construction cost estimation papers in 23 journals. Only 33 papers focused on factors influencing the performance of cost estimation. These papers were then analyzed, synthesized, and summarized in terms of the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…The findings also show that avoidance of cost overruns was possible through estimating resource (M=3.72, SD=1.054) and the respondents also agreed that cost estimates were done according the specific project phase and a report was made, (M=3.66, SD =1.005). The researchers ' Fazil, et al (2021) revealed that estimating cost of project is critical and helps in avoiding cost overruns. The cost estimates can be drawn from past projects by assessing the costs incurred and estimated project costs.…”
Section: Project Cost Estimationmentioning
confidence: 99%
“…The findings also show that avoidance of cost overruns was possible through estimating resource (M=3.72, SD=1.054) and the respondents also agreed that cost estimates were done according the specific project phase and a report was made, (M=3.66, SD =1.005). The researchers ' Fazil, et al (2021) revealed that estimating cost of project is critical and helps in avoiding cost overruns. The cost estimates can be drawn from past projects by assessing the costs incurred and estimated project costs.…”
Section: Project Cost Estimationmentioning
confidence: 99%
“…This underperformance not only jeopardizes the project's success but also causes financial damage, particularly for design consultancy firms [5]. Fazil [6] identified several factors affecting cost estimation performance, including the experience and skill levels of estimators, experience in similar projects, the project teams, financial capability, project complexity, project information, task characteristics, cost estimation methods, project size, and external factors. While many previous studies have explored the relationship between these factors and cost estimation performance [4,7], relatively limited research has delved into the details of task characteristics within the context of cost estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia is a developing country that continues to grow its infrastructure. Calculating the construction cost of buildings as closely as possible to its actual price is especially important, as poor cost estimate performance has caused project failure before [1]- [10]. Several estimates are needed based on the intended use and designation in construction practices.…”
Section: Introductionmentioning
confidence: 99%